Ecological Niche Conservatism and Evolutionary Dynamics in Octopodidae: A Phylogenetic Comparative Approach - Aura Pamela Santiago‐Sarmiento; Citlalli Edith Esparza‐Estrada; Carlos Alberto Yáñez‐Arenas; Luis Enrique Ángeles‐González; Lucas Jardim (Journal of Biogeography, 2026)
Aim Understanding how ecological niches evolve is crucial for predicting species' responses to environmental change. Cephalopods, particularly those in the Octopodidae family, offer a compelling model system due to their short life spans, phenotypic plasticity and divergent developmental modes. We examined the evolutionary dynamics of the fundamental niche (FN) in Octopodidae by assessing niche overlap among closely related species pairs, quantifying phylogenetic niche conservatism (PNC) for temperature and dissolved oxygen, and evaluating phylogenetic signal and best‐fitting evolutionary models across the family. Location Temperate, tropical and subtropical oceanic waters. Time Period Occurrence records span from 1858 to 2024, with more than 80% of the records from 2000 to 2024. Environmental variables were obtained from monthly data available for 2000–2020, with the subset from 2010 to 2020 used in the analyses. Major Taxa Studies Octopodidae (d'Orbigny, 1839). Methods We conducted pairwise niche overlap analyses, incorporating both occurrence data and multiple definitions of the accessible area. Phylogenetic signal was estimated using Pagel's λ and Blomberg's K, and evolutionary models (Brownian Motion, BM; Ornstein‐Uhlenbeck, OU; and Early Burst, EB) were fitted for each niche trait. Results Sister‐species comparisons revealed no statistically significant niche overlap ( p > 0.05), suggesting niche lability at shallow phylogenetic levels, while evolutionary model selection supported the Ornstein–Uhlenbeck model for all traits ( α : 0.018–12.399), which is also consistent with the influence of stabilizing selection. Our analyses indicated stronger environmental constraints on temperature‐related traits, suggesting greater limitations under thermal stress, whereas oxygen‐related traits exhibited more variable patterns of phylogenetic constraints across niche dimensions. Main Conclusions Collectively, these findings support a mosaic pattern of niche evolution, challenging traditional assumptions of strong PNC in marine organisms. Taken together, stronger constraints under thermal stress suggest that cephalopods may have a limited capacity for rapid evolutionary adaptation to ongoing climate warming. This study provides the first comprehensive assessment of FN evolution in cephalopods, highlighting ecological constraints that may influence their adaptive capacity under future climate change scenarios.

Variation in Environmental Conditions and Biodiversity Between Contrasting Intertidal Habitats Across Multiple Spatial Scales on European Rocky Shores - Luca Rindi; Ludovica Pedicini; Iacopo Bertocci; Lisandro Benedetti‐Cecchi; Dan Smale; Fernando Tuya; Adriana Rodriguez; Mariachiara Chiantore; Valentina Asnaghi; Paolo Albicini; Rolf Karez; Dominique Davoult; et al. (Global Ecology and Biogeography, 2026)
Aim Foundation species sustain biodiversity by providing habitat, resources, and protection from environmental stress. However, their influence on environmental severity and variability and their role in shaping diversity across spatial scales remain poorly understood. We conducted a large‐scale study to assess how environmental conditions and community diversity vary between areas with and without canopy‐forming macroalgae across local to regional spatial scales. Location Latitudinal range from 28°34′N to 54°11′N, encompassing both the Northeast Atlantic and Western Mediterranean regions. Time Period 2019–2020. Major Taxa Studied Marine macroalgae and benthic invertebrates. Methods Using a standardised nested sampling design across 13 sites in two marine regions (the Northeast Atlantic and Western Mediterranean) we compared the intensity and variability of temperature and light intensity, as well as community α‐ and β‐diversity, between intertidal rocky areas with and without canopy‐forming macroalgae. Data were analysed by means of linear mixed‐effects models. Results There were regional differences in variations of environmental conditions between habitats: NE Atlantic macroalgal canopies were characterised by lower environmental extremes and variability—especially in summer—than open rock areas, whereas differences between habitats were small in the W Mediterranean. Likewise, differences in α‐ and β‐diversity between habitats were region‐specific and scale‐dependent: in the NE Atlantic, α‐diversity was higher in the presence of canopies than in open rock areas from local to regional scales, while β‐diversity decreased in canopy stands with increasing spatial scale. In the W Mediterranean, α‐diversity was higher under canopies than on open rock at the regional scale, whereas β‐diversity was higher under canopies at small to intermediate scales. Main Conclusions Our results support the view that key environmental conditions and biodiversity on intertidal rocky shores differ between areas characterised by the presence or absence of canopy‐forming macroalgae acting as foundation species, across a hierarchy of spatial scales.

Influence of yeast adaptation with bio-activators on the process of wine alcoholic fermentation - Enrico Viola; Vincenzo Naselli; Valentina Craparo; Filippo Amato; Riccardo Savastano; Antonino Pirrone; Azzurra Vella; Irene Dolce; Venera Seminerio; Micaela Carusi; Rosaria Arena; Raimondo Gaglio; et al. (Food Microbiology, 2025)

Optimisation of the quantum yield of carbon quantum dots prepared from bergamot pomace by means of a full factorial experimental design - Emanuele Zanda; Anna Irto; Salvatore Giovanni Michele Raccuia; Clemente Bretti; Giovanna De Luca; Ileana Ielo; Mariosimone Zoccali; Alessia Arena; Giuseppe Paladini; Francesco Caridi; Mauro Formica; Eleonora Macedi; et al. (Journal of Environmental Chemical Engineering, 2025)

Suitability of two different organic substrates as growing media for sustaining the productivity of mediterranean plant species in degraded sites - Giulia Maisto; Luca Vitale; Lucia Santorufo; Valeria Memoli; Ermenegilda Vitale; Giorgia Santini; Giulia Costanzo; Anna De Marco; Carmen Arena (Environmental Sustainability, 2025)
The degradation of natural and urban areas due to human activities has intensified in recent decades, leading to significant biodiversity loss and decline in ecosystem service. In this context, the revegetation with native Mediterranean sclerophyllous shrubs represents a promising strategy for the recovery of overexploited environments. This study evaluated the suitability of two organic substrates—compost (C) and a compost-poultry manure mix (CP)— obtained from domestic waste and green refuse, as growing media for three Mediterranean species ( Quercus ilex L., Phillyrea angustifolia L., Laurus nobilis L.) to restore degraded sites. To assess the effects of substrate type and climate on primary production, three plant species were cultivated for one year in mesocosms containing limestone debris, which was amended with either C or CP, and leaf gas exchanges as well as key eco-physiological traits were monitored across seasons. Results showed that plants on CP exhibited higher photosynthetic rates compared to those on C substrate, with increases of 25%, 12%, and 20% for Q. ilex , P. angustifolia , and L. nobilis , respectively, accompanied by greater height and trunk diameter for all species. Notably, during the summer drought period, CP plants maintained enhanced carbon fixation—22%, 25%, and 37% higher than C plants for the respective species. One year after, organic matter (OM) in the CP substrate had decreased by 44%, compared to only 7% in the C substrate, suggesting more rapid utilization by the plants. The readily available OM and the higher water-holding capacity of CP substrate (+ 54% after one year)), presumably contributed to the improved photosynthetic and transpiration rates during summer. Among species, Q. ilex demonstrated the highest resilience under challenging environmental conditions. Overall data suggests that the CP substrate is more effective than the C in promoting plant growth and offers significant potential for the recovery of degraded sites, such as disused quarries.

Assessing the resilience of the coralline macroalga Ellisolandia elongata in response to a prolonged low tide - Rosa Donadio; Ermenegilda Vitale; Giulia Costanzo; Luca Licciardi; Erika Fabbrizzi; Simonetta Fraschetti; Carmen Arena (Environmental Research, 2025)

Foraminifera and sediments cored from the bottom of the Faanu Mudugau Blue Hole, Ari Atoll, Maldives: Diversity, taphonomy and environmental reconstruction of an inhabitable substrate - Victor M. Giraldo-Gómez; Luca Arena; Marco Capello; Laura Cutroneo; Annalisa Azzola; Monica Montefalcone; Antonino Briguglio (Marine Geology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A Paleogene mixed carbonate-siliciclastic system in the western Tethys: spectral gamma-ray as a tool for the reconstruction of paleoclimate and transgressive-regressive cycles - Victor M. Giraldo-Gómez; Michele Piazza; Luca Arena; Andrea Baucon; Antonella Gandolfi; Cesare A. Papazzoni; Johannes Pignatti; Antonino Briguglio (Marine and Petroleum Geology, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Short-term middle Eocene (Bartonian) paleoenvironmental changes in the sedimentary succession of Olivetta San Michele (NW Italy): the response of shallow-water biota to climate in NW Tethys - Luca Arena; Victor M. Giraldo-Gómez; Andrea Baucon; Michele Piazza; Cesare A. Papazzoni; Johannes Pignatti; Antonella Gandolfi; Antonino Briguglio (Facies, 2024)
This study focuses on the paleontological content of the middle Eocene (Bartonian) carbonate–siliciclastic sediments of the Capo Mortola Calcarenite Formation from Olivetta San Michele (Liguria, Italy). Along the succession, there are significant paleoecological changes triggered by the variation in neritic input as a consequence of tectonic and climatic instability. Among microfossils, nummulitids prevail, followed by orthophragmines, smaller benthic, and planktonic foraminifera, whereas mollusks and ichnofossils are the most abundant macrofossils. The sudden changes in the benthic communities due to the progressive increase in fluvial input are recorded throughout the sedimentary succession. An increase in water turbidity caused stressful conditions for autotrophic taxa, reducing their size and abundance. In contrast, filter feeders became dominant, suggesting an increase in dissolved and suspended nutrients. Ichnological analysis shows environmental fluctuations controlled by the transport of neritic material offshore, thus confirming the general deepening trend of the studied succession. In the upper part of the succession, we recorded an alternation between gravity flows and marly sediments that are interpreted as short-term alternations between low and intense precipitations. The gravity flows yield taxa such as larger benthic foraminifera (LBF), smaller benthic and planktonic foraminifera, mollusks, and corals. In turn, marls display only a few LBF and abundant smaller benthic and planktonic foraminifera. In these intervals, the increase in planktonic foraminifera also suggests a deepening of the carbonate ramp coinciding with a reduction of light that did not favor the development of LBF. These changes are probably related to the climatic dynamics that occurred in the Bartonian in the western Tethys.

Polyhydroxybutyrate/valerate production from methanol by Methylorubrum extorquens: Process limiting factors and polymer characterisation - Ana Maria Zetty Arenas; Heleen De Wever; Luca Brendolise; Antonia Keil; Wouter Van Hecke (Bioresource Technology Reports, 2023)

Extracellular cGMP Reverses Altered Membrane Expression of AMPA Receptors in Hippocampus of Hyperammonemic Rats: Underlying Mechanisms - Lucas Taoro-Gonzalez; Yaiza M. Arenas; Andrea Cabrera-Pastor; Vicente Felipo (Molecular Neurobiology, 2019)

Assessment of Eco-Physiological Performance of Quercus ilex L. Leaves in Urban Area by an Integrated Approach - Carmen Arena; Anna De Maio; Flavia De Nicola; Lucia Santorufo; Luca Vitale; Giulia Maisto (Water, Air, & Soil Pollution, 2014)

Taking into account water use impacts in the LCA of biofuels: an Argentinean case study - Mireille Faist Emmenegger; Stephan Pfister; Annette Koehler; Luca de Giovanetti; Alejandro Pablo Arena; Rainer Zah (The International Journal of Life Cycle Assessment, 2011)

Growth and gas exchange response to water shortage of a maize crop on different soil types - Luca Vitale; Paul Di Tommasi; Carmen Arena; Michele Riondino; Annachiara Forte; Angelo Verlotta; Angelo Fierro; Amalia Virzo De Santo; Amodio Fuggi; Vincenzo Magliulo (Acta Physiologiae Plantarum, 2009)

Effects of water stress on gas exchange of field grown Zea mays L. in Southern Italy: an analysis at canopy and leaf level - Luca Vitale; Paul Di Tommasi; Carmen Arena; Angelo Fierro; Amalia Virzo De Santo; Vincenzo Magliulo (Acta Physiologiae Plantarum, 2007)